Exploring associations between water, sanitation, and anemia through 47 nationally representative demographic and health surveys. Issue 1 (24th June 2019) - Kothari, Monica T.; Coile, Amanda; Huestis, Arja; Pullum, Tom; Garrett, Dean; Engmann, Cyril
Abstract: Globally, no countries are on track to achieve the adopted global nutrition targets set for anemia in 2025. Given the linkages between water, sanitation, and hygiene (WASH) and nutrition, this secondary data analysis explores potential associations with anemia. Forty‐seven demographic and health surveys were used to explore the association between unimproved water and sanitation and anemia in women and children with adjusted odds ratios (ORs) calculated by country and cumulatively. In over 60% of countries, children with off‐premises water access had significantly increased odds of anemia. In over a quarter of countries, children exposed to surface water had higher odds of anemia. In Burundi, children were 1.65 times more likely to be anemic when reported to be living in households using surface water. However, in India, a protective effect was noted (adjusted OR: 0.70, P < 0.001) for surface water. In 60% and 65% of countries, women and children exposed to an open sanitation facility had higher odds of being anemic, respectively. There is evidence of an association between selected water and sanitation indicators and anemia. Promoting policies, practices and research that strengthen access to improved WASH should be considered for reducing anemia prevalence alongside standard nutrition interventions. Abstract : Given the linkages between water, sanitation, and hygiene and nutrition, this secondary data analysis explores potential associations with anemia. Forty‐seven demographic and health surveys were used to explore the association between unimproved water and sanitation and anemia in women and children with adjusted odds ratios calculated by country and cumulatively.